Dinâmica vegetacional e diversidade florística em áreas de vegetação campestre, Rio Grande do Sul, Brasil - Goulart, Carolina Gomes (2014)
The Pampa biome encompasses heterogeneous ecosystems, because of the great number of kinds of soils and the variations in altitude and also in the climate, and such characteristics are directly reflected in the floristic composition of the different vegetal communities. The knowledge of such diversity and the comprehension of the dynamics in this vegetation along with the practices of conservationist management result in a better use of the natural resources of the native meadow areas. This study aimed to assess those vegetation dynamics in an experimental area of natural meadow managed with different grazing methods, at Embrapa CPPSUL, Bagé, RS and concomitantly assess the floristic diversity of areas of native meadows submitted to fertilization and grazing methods in Unidades Experimentais Participativas in the Alto Camaquã area, RS, Brasil. In the study of the vegetation dynamics in the experimental area at Embrapa CPPSUL, the estimates of the species composition and their respective biomasses have followed the field proceedings of the BOTANAL method, with some adaptations. In order to generate hypotheses about the effects of the treatments (continuous and controlled grazing), multivariate analyzes have been used for the data about the species dynamics and functional types. The diversity and uniformity of species have been quantified through the indices of Shannon and equitability. There weren t evidences of meaningful differences among the factors: grazing, time and interaction grazing x time. There weren t also meaningful differences between rotary and continuous methods of grazing. The most frequent families in the survey in the studied areas of the Alto Camaquã area were, respectively: Poaceae, Asteraceae, Cyperaceae, and Fabaceae. Considering the fertilizing factor, there weren t differences among the different kinds of fertilization. The areas that are kept under continuous grazing show less diversity in comparison with the ones with rotary grazing.